Makarenko Y. G., Matkovska I. V. To the translation problem of Internet and computer neologisms - Makarenko Y. G.; Matkovska I. V. (Philological Treatises, 2020)
The article deals with the notion of “neologism”, its basic particularities and division into groups in correspondence with the patterns of appearance. Main translation techniques of Internet and computer neologisms are analyzed